AN ANALYSIS OF GRAMMATICAL COHESIVE DEVICES IN AN EXPOSITORY ESSAY WRITTEN BY AI WRITING TOOL ‘CHAT GPT’ - Noreen Zahra; Rabia Shabbir; Mehak Sohail; Faiza Latif (International Journal of Contemporary Issues in Social Sciences, 2024)
Artificial intelligence is the emerging field of the modern world with the ability to revolutionize the writing of various types and the advancement of AI has initiated the creation of unique tools that can help to write different discourses. The current study aims to identify the grammatical cohesive devices employed in an expository essay titled “Social Media: Blessings and Curses” written by one of the most popular artificial intelligence tools named ChatGPT. ChatGPT is a language model developed by OpenAI, Inc, California creating human-like discourse according to the prompt given to it. The study used Halliday and Hasan's (1976) cohesion theory as the theoretical framework. The research paradigm is qualitative and the descriptive content analysis has been used as the method of the study. The data for the analysis was the essay consisting of 558 words. The results indicated that the expository essay written by the AI tool named ChatGPT exhibited the efficient use of grammatical cohesion. The most used grammatical cohesive device was the anaphoric reference while no ellipsis was used. The research recommends to take help from this tool to teach students the concept of cohesion and coherence in academic writing.